2020
DOI: 10.3847/1538-4357/ab818f
|View full text |Cite|
|
Sign up to set email alerts
|

Burst Properties of the Most Recurring Transient Magnetar SGR J1935+2154

Abstract: We present timing and time-integrated spectral analysis of 127 bursts from SGR J1935+2154. These bursts were observed with the Gamma-ray Burst Monitor on the Fermi Gamma-ray Space Telescope and the Burst Alert Telescope on the Neil Gehrels Swift Observatory during the source's four active episodes from 2014 to 2016. This activation frequency makes SGR J1935+2154 the most burst prolific transient magnetar. We find the average duration of all the detected bursts to be much shorter than the typical, anticipated v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
57
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 53 publications
10
57
0
2
Order By: Relevance
“…The rotation period (3.24 s) and surface dipole magnetic field (2.2 × 10 14 G) of SGR 1935+2154 is typical of the Milky Way magnetar population 2 . Although SGR 1935+2154 was in a phase of increased X-ray burst activity when ST 200428A was detected, increased burst activity has previously been observed from this SGR 30 . Indeed, SGR 1935+2154 is the most prolific known burster among the magnetar population 30 .…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…The rotation period (3.24 s) and surface dipole magnetic field (2.2 × 10 14 G) of SGR 1935+2154 is typical of the Milky Way magnetar population 2 . Although SGR 1935+2154 was in a phase of increased X-ray burst activity when ST 200428A was detected, increased burst activity has previously been observed from this SGR 30 . Indeed, SGR 1935+2154 is the most prolific known burster among the magnetar population 30 .…”
mentioning
confidence: 60%
“…Although SGR 1935+2154 was in a phase of increased X-ray burst activity when ST 200428A was detected, increased burst activity has previously been observed from this SGR 30 . Indeed, SGR 1935+2154 is the most prolific known burster among the magnetar population 30 . The X-ray burst coincident with ST 200428A (isotropicequivalent energy release of 8.3(8) × 10 39 erg) was a typical example of a magnetar burst 2 , with perhaps some unusual spectral characteristics 6 .…”
mentioning
confidence: 60%
“…However, a thermal origin is preferred for normal short bursts from magnetars 26,27 . We notice that ∼ 6% of the bursts (7/109) from SGR J1935+2154 detected with Fermi/GBM between 2014 and 2016 can be best fit with a power-law model 13 19 , then the observed fluence should be ∼ 4 × 10 −15 erg cm −2 in 1-250 keV, which is far below the sensitivity limits of the X-ray telescopes currently in orbit (or in the foreseeable future). This may explain the non-detection of the X-ray counterpart of any cosmological FRB so far.…”
Section: Insight-hxmt Detected a Series Of 11 Bursts Within About 17 mentioning
confidence: 78%
“…Since its discovery, the source has sporadically gone into outburst over the past few years (Lin et al 2020a), with the most recent being reported as a "forest" of X-ray bursts detected during 2020 April 27-28 (Palmer & Team 2020;Younes et al 2020). Following the onset of the outburst, an unprecedented bright millisecond-duration radio burst (hereafter FRB 200428) was detected from the source by the Canadian Hydrogen Intensity Mapping Experiment (CHIME; The CHIME/FRB Collaboration et al 2020) and STARE2 (Bochenek et al 2020) telescopes, with an energy release that was ∼1000× brighter than any known radio burst from a Galactic source.…”
Section: Introductionmentioning
confidence: 99%